Health insurance, a friend in need? Evidence from financial and health diaries in Kenya - Geng, Xin; Ide, Vera; Janssens, Wendy; Kramer, Berber; van der List, Marijn (International Food Policy Research Institute, 2017)
Health insurance can protect consumption from health shocks, but it can also crowd out informal transfers. This paper examines whether health insurance improves consumption smoothing in the face of health shocks, and to what extent results depend on households’ access to informal transfers as a risk coping strategy. Using high-frequency panel data on health and finances collected in rural Kenya, we show that mobile money users have stronger access to informal transfers than nonusers. We further find that health shocks induce nonusers of mobile money to lower their nonhealth expenditures by approximately 25 percent in weeks when they are uninsured. These same households are able to smooth consumption in weeks with insurance coverage, due to lower out-of-pocket health expenditures. In contrast, mobile money users are able to smooth consumption when experiencing health shocks even in the absence of health insurance, due to an inflow of informal transfers. For this group, health insurance improves healthcare utilization and does not crowd out the inflow informal transfers during weeks with health shocks. These findings have implications for the design of health insurance and mobile health financing products.